Implementation Image Based Tracking Augmented Reality on The Promotion Brochure of Honda Matic Motorcycles - Riko Raynol Hasan; Reza Andrea; Syafei Karim (TEPIAN, 2020)
In this research is motivated by the absence of other alternatives in terms of supporting the promotion of Honda automatic motorcycles because until now the Honda dealer PT. Tunas Dwipa Matra only uses brochures as a promotional medium and this still has a shortage of potential customers who can only see the motorcycles with 2D images and cannot see every angle on the motorcycles. So in this case the customer certainly needs an application so that they can help see the visual appearance in 3D and also help them see the product in an informative manner that is directly contained in the application, with that there is a technology that can be used called Augmented Reality (AR). AR is a combination of 3D or 2D virtual objects and virtual objects that will blend into the real world. This study uses the image-based tracking method which is part of marker-based tracking where the marker is a brochure using a brochure that is readily available from the company. From this research, an Augmented Reality application for a Honda Matic motorcycles named Ar Motic will be built using the Unity application with the Vuforia Software Development Kit (SDK) for tracking brochures to display 3D objects and the Blender application that helps in making 3D models (Selvia, 2019).